An Analysis of Sociodemographic and Clinical Characteristics in Children and Adolescents Diagnosed with Childhood Onset Speech Fluency Disorder - Gürbüz Özgür, Börte; Özgür, Erdoğan (ENT Updates, 2019)
Objective: Childhood onset speech fluency disorder (stuttering) is a communication disorder beginning in childhood, and is characterised by interruption to speech flow, sound prolongations and pauses produced by repetition of a particular sound or word. The aim of this study was to investigate the sociodemographic characteristics, comorbid psychiatric diagnoses and other variables that are associated with stuttering. Methods: Sixty-four children and adolescents aged under 18 years and attending the child and adolescent psychiatry or otorhinolaryngology (ENT) outpatient clinic between November 2017 and June 2019 were enrolled in the study. ENT examination was carried out. A sociodemographic questionnaire was also administered to the participants. The psychiatric evaluation of the patients was performed according to DSM-5 criteria. Results: The mean age was 7.36±3.76 years. 70.3% of the cases were male. The mean age at onset of stuttering was 4.85±2.34 years and the average stuttering duration was 2.31 years. In 31.3% of cases a life stressor had preceded stuttering, 21.9% had a positive family history, and 40.6% had comorbid psychiatric morbidity. The most common comorbid psychiatric diagnoses were specific learning disorder, speech sound disorder and attention deficit hyperactivity disorder. Conclusion: According to the results obtained, stuttering was 2.3 times more common in males, and 68.7% of all cases were below the age of 5 years. The most common psychiatric diagnoses found in cases of stuttering are within the neurodevelopmental disorders grouping. Since psychiatric diagnoses occur at such a high frequency, it is important to address this comorbidity when treating stuttering